Analysis of Water Quality Correlation with the Immune Response of Litopenaeus vannamei in Probolinggo, East Java - Putra, Andhika Farras Rahardian; Hertika, Asus Maizar Suryanto; Maimunah, Yunita (International Journal of Marine Engineering Innovation and Research, 2025)
Whiteleg shrimp (Litopenaeus vannamei) is a major aquaculture commodity in Indonesia, valued for its resilience, rapid growth, and economic potential. However, water quality remains a critical factor influencing shrimp health, particularly their immune response. This study aimed to examine the correlation between water quality parameters and the immune responses of L. vannamei cultivated in Probolinggo, East Java. A descriptive quantitative method was employed, using simple random sampling across three pond sites. Water parameters measured included temperature, pH, dissolved oxygen (DO), salinity, ammonia, nitrate, total suspended solids (TSS), and total dissolved solids (TDS). Immune response indicators such as Total Hemocyte Count (THC), differential hemocyte count (DHC), and phagocytic activity were analyzed. Canonical Correspondence Analysis (CCA) was used to assess correlations. The results revealed significant relationships between water quality and shrimp immune parameters, highlighting the importance of proper environmental management in shrimp farming. These findings provide insights for improving productivity and disease resistance in sustainable aquaculture systems.